Η ΑΓΓΑΡΕΙΑ ΣΤΗΝ ΚΕΡΚΥΡΑ ΚΑΤΑ ΤΟΝ ΟΨΙΜΟ ΜΕΣΑΙΩΝΑ - ΑΣΩΝΙΤΗΣ ΣΠΥΡΟΣ Ν. (Eoa kai Esperia, 2000)
The author deals with the ancient institution of angaria (labour service) as it wasapplied in the Greek island of Corfu during the late middle ages, when Corfu, aformer byzantine province, was dominated by the Angevins of Naples (1272-1386)and then by Venice (1386-1797). Two basic types of angaria are discerned, oneclaimed by the fisc from the tax-payers, the other by the landowners from thetenants. The mechanisms used for the accomplishment of the angaria, the impactof the obligatory angaria of both types on the social status of the population, as wellas the social differentiation effected by the privileges of exemption from theangaria, are some aspects of that institution examined in this study, which iscompleted with the publication of three documents concerning privileges ofexception from the angaria.